ANALISIS IMPLEMENTASI SISTEM INFORMASI AKUNTANSI KOMPUTERISASI PADA KANTOR PELAYANAN PAJAK PRATAMA KARANGANYAR - Setiawan, Ade; Ningrum, Azfrizda Yuhan Diwanti Karlinda (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
This study aims to analyze the influence of infrastructure, human resources, cost, perceptions of usefulness, perceptions of ease of implementation of computerized accounting information system. Population in this research is 114 employees of KPP Pratama Karanganyar. Based on purposive sampling method, this study used 35 respondents who worked as an employee of accounting and finance. For dependent variable of this study is the implementation of computerized accounting information system (y). While for the independent variables of infrastructure (x 1 ), human resources(x 2 ), cost (x 3 ), perceptions of usefulness (x 4 ), perceptions of ease (x 5 ). The method used is quantitative research methods. This study used primary data with quetionary. Data was analyzed multiple regression analysis with software IBM SPSS Statistic ver 20 processing. The results of this study indicate that human resources and perception of ease have a positive and significant impact on the implementation of computerized accounting information system. But infrastructure, cost and perceptions of usefulness have no effect on the the implementation of computerized accounting information system.